2023
DOI: 10.3390/nu15071742
|View full text |Cite
|
Sign up to set email alerts
|

Is Autologous Fecal Microbiota Transfer after Exclusive Enteral Nutrition in Pediatric Crohn’s Disease Patients Rational and Feasible? Data from a Feasibility Test

Abstract: Background: Exclusive enteral nutrition (EEN) is a highly effective therapy for remission induction in pediatric Crohn’s disease (CD), but relapse rates after return to a regular diet are high. Autologous fecal microbiota transfer (FMT) using stool collected during EEN-induced clinical remission might represent a novel approach to maintaining the benefits of EEN. Methods: Pediatric CD patients provided fecal material at home, which was shipped at 4 °C to an FMT laboratory for FMT capsule generation and extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…A clinical trial administering FMT in active UC has shown enhancement and reduction in specific CAM genera as well as their respective negative and positive correlations with fecal calprotectin levels and clinical/endoscopic disease activity scores, thus highlighting the potential link of CAM with the course of UC and its FMT-mediated restitution [ 39 ]. Perhaps unsurprisingly, autologous FMT has not been found useful in IBD due to the dysbiotic nature of the patient’s microbiome [ 46 ]. The contribution of modulation of the immune system by FMT remains to be explored.…”
Section: Mechanism Of Action Of Fmt In Ibdmentioning
confidence: 99%
“…A clinical trial administering FMT in active UC has shown enhancement and reduction in specific CAM genera as well as their respective negative and positive correlations with fecal calprotectin levels and clinical/endoscopic disease activity scores, thus highlighting the potential link of CAM with the course of UC and its FMT-mediated restitution [ 39 ]. Perhaps unsurprisingly, autologous FMT has not been found useful in IBD due to the dysbiotic nature of the patient’s microbiome [ 46 ]. The contribution of modulation of the immune system by FMT remains to be explored.…”
Section: Mechanism Of Action Of Fmt In Ibdmentioning
confidence: 99%